The Whole Brain Teaching: Approach for Improving the Memorization Skills of Learners with Mild Intellectual Disability (MID) - Mugot, Maridel Rebollido (JPAIR Multidisciplinary Research, 2019)
Remembering information can be difficult, especially for a learner with Mild Intellectual Disability. One classroom instruction approach which maximizes students' engagement, focuses on the way the brain is intended to learn and addresses the difficulty in memorizing is Whole Brain Teaching. This study was conducted to determine the effects of WBT as an approach to improve the memorization skills of learners with Mild Intellectual Disability at City Central School - Special Education Center. Quasi-experimental research design was employed in the study. Eight (8) learners who were diagnosed with MID were randomly selected and assigned as experimental and control groups. Pretest and post-test were used in measuring the academic performance of the learners. The experimental group was taught using the WBT approach and the control group was taught using the conventional approach. The results revealed that the academic performance in both groups increased significantly after subjecting them to WBT approach and conventional approach respectively. However, the results of the post-test comparison of both groups showed that there was a statistically significant difference between the academic performance of the experimental and control groups in favor of the experimental group. Thus, WBT has positive impact on the improvement of the memorization skills of learners with MID.
Keywords: Education; Teaching Strategies; Quasi-experimental design; Cagayan de Oro City; Philippines